Degree of biliary tract violation during treatment of gallbladder adenocarcinoma is independently associated with development of peritoneal carcinomatosis. Issue 4 (11th June 2021) - Sutton, Thomas L.; Walker, Brett S.; Radu, Stephanie; Dewey, Elizabeth N.; Enestvedt, C. Kristian; Maynard, Erin; Orloff, Susan L.; Nabavizadeh, Nima; Sheppard, Brett C.; Lopez, Charles D.; Billingsley, Kevin G.; Mayo, Skye C.
Abstract: Background: Gallbladder cancer (GBC) is often incidentally diagnosed after cholecystectomy. Intra‐operative biliary tract violations (BTV) have been recently associated with development of peritoneal disease (PD). The degree of BTV may be associated with PD risk, but has not been previously investigated. Methods: We reviewed patients with initially non‐metastatic GBC treated at our institution from 2003 to 2018. Patients were grouped based on degree of BTV during their treatment: major (e.g., cholecystotomy with bile spillage, n  = 27, 29%), minor (e.g., intra‐operative cholangiogram, n  = 18, 19%), and no violations ( n  = 48, 55%). Overall survival (OS) and peritoneal disease‐free survival (PDFS) were evaluated with Kaplan‐Meier and Cox proportional hazards modeling. Results: Ninety‐three patients were identified; the median age was 64 years (range 31–87 years). Seventy‐six (82%) were incidentally diagnosed. The median follow‐up was 23 months; 20 (22%) patients developed PD. The 3‐year PDFS for patients with major, minor, and no BTV was 52%, 83%, and 98%, respectively (major vs. none: p  <  0.001; minor vs. none: p  <  0.01). BTV was not associated with 5‐year OS (HR 1.53, p  =  0.16). Conclusion: Increasing degree of BTV is associated with higher risk of peritoneal carcinomatosis in patients with GBC and should be considered during preoperative risk stratification. Reporting biliary tract violations during cholecystectomy is encouraged.